Plasmin Inhibitor in Health and Diabetes: Role of the Protein as a Therapeutic Target - Alsayejh, Basmah; Kietsiriroje, Noppadol; Almutairi, Mansour; Simmons, Katie; Pechlivani, Nikoletta; Ponnambalam, Sreenivasan; Ajjan, Ramzi A. (TH Open, 2022)
The vascular obstructive thrombus is composed of a mesh of fibrin fibers with blood cells trapped in these networks. Enhanced fibrin clot formation and/or suppression of fibrinolysis are associated with an increased risk of vascular occlusive events. Inhibitors of coagulation factors and activators of plasminogen have been clinically used to limit fibrin network formation and enhance lysis. While these agents are effective at reducing vascular occlusion, they carry a significant risk of bleeding complications. Fibrin clot lysis, essential for normal hemostasis, is controlled by several factors including the incorporation of antifibrinolytic proteins into the clot. Plasmin inhibitor (PI), a key antifibrinolytic protein, is cross-linked into fibrin networks with higher concentrations of PI documented in fibrin clots and plasma from high vascular risk individuals. This review is focused on exploring PI as a target for the prevention and treatment of vascular occlusive disease. We first discuss the relationship between the PI structure and antifibrinolytic activity, followed by describing the function of the protein in normal physiology and its role in pathological vascular thrombosis. Subsequently, we describe in detail the potential use of PI as a therapeutic target, including the array of methods employed for the modulation of protein activity. Effective and safe inhibition of PI may prove to be an alternative and specific way to reduce vascular thrombotic events while keeping bleeding risk to a minimum.Key Points
Keywords: α2-antiplasmin; plasmin inhibitor; diabetes